"The expert and the patient": a discourse analysis of the house of commons' debates regarding the 2007 Mental Health Act. (4th March 2022) - Kent, Tom; Cooke, Anne; Marsh, Ian
Abstract: Background: The Mental Health Act 1983 was amended in 2007. This legislation appears to be predicated on the assumption that an entity of "mental disorder" exists and that people who are designated mentally disordered require medical treatment, administered by force if necessary. Aims: To explore the ways in which mental disorder is constructed and the possible practical effects of these constructions in the House of Commons' debates regarding the Mental Health Act 2007. Method: Verbatim transcripts from the House of Commons debates on the Mental Health Act were studied through a discourse analysis. Results: Two primary discursive constructions were identified: "The Expert" and "The Patient." Conclusion: Mental disorder and associated roles, such as "The Expert, " were constructed through particular selective rhetoric, which taken together, made particular psychiatric practices and the need for legislation, such as compulsory detention, seem normal, and necessary.